Случаи обнаружения трематоды Ogmogaster antarcticus Johnston, 1931 (Notocotylidae Luhe, 1909) в печени сейвала (Balaenoptera borealis Lesson) - Скрябин, А.С. (Вестник зоологии, 1970)
Описаны случаи извращенной локализации неполовозрелых трематод Ogmogaster antarcticus Johnston , 1931 в печени у сейвалов (Balaenoptera borealis Less.) , добытых в водах Антарктики. Дано описание молодых марит из печени. Cases of perverted localization are discribed in sexually immature trematodes Ogmogaster antarcticus Johnston , 1931. in liver of Balaenoptera borealis Less. , obtained from waters of the Antarctic. The description of young maritas from liver is given.